Fiduciary obligations in business / edited by Arthur B. Laby, Rutgers Law School, Jacob Hale Russell, Rutgers Law School. - Laby, Arthur B.; Russell, Jacob Hale (Cambridge University Press, 2021)
The scholarship on fiduciary duties in business organizations is often pulled in two directions. While most observers would agree that business organizations are one of the key contexts for the application of the fiduciary obligation, corporate law theorists have often expressed disdain for the role of fiduciary duties, with the result that fiduciary law and theory have been out of step with the business world. This volume aims to rectify this situation by bringing together a range of scholars to analyze fiduciary relationships and the fiduciary obligation in the business context. Contributing authors examine fiduciary obligations in fields ranging from entity structure to bankruptcy to investment regulation. The volume demonstrates that fiduciary law can inform pressing corporate governance debates, including discussions over stakeholder models of the corporation that move beyond shareholder interests.